2019
DOI: 10.1007/s12649-018-0537-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aromatic Structure on the Thermal Behaviour of Lignin

Abstract: Lignin, a natural biopolymer and abundant by-product, is a particularly promising feedstock for carbon-based materials and a potentially sustainable alternative to phenolic resins, which are typically derived from crude oil. The source and method used to isolate lignin have a large impact on the thermal properties of the polymer, and can affect resultant materials prepared from lignin. Previous investigations into lignin characterisation often utilise a variety of feedstocks and isolation methods, which can ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
1
12
1
Order By: Relevance
“…The G-band is due to the vibrations of sp 2 bonded carbon atoms in the 2D hexagonal lattice and the D-band represents the in-plane terminated disordered tangling bonds in graphite. In both KLCAs and SLCAs, the ratio of intensity of the G-band to D-band (I G /I D ) is more than 1, indicating the presence of partially graphitized carbon structures formed as a result of rearrangement of the carbon structure during the carbonization process, which is advantageous for making superior supercapacitor (SC) electrodes [ 48 ]. XRD patterns of KL and SL were recorded and represented in Figure 2 e. In the case of KL, a diffraction peak was observed at 2θ = 18.7°, while for SL the peak was located at 2θ = 21.6°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G-band is due to the vibrations of sp 2 bonded carbon atoms in the 2D hexagonal lattice and the D-band represents the in-plane terminated disordered tangling bonds in graphite. In both KLCAs and SLCAs, the ratio of intensity of the G-band to D-band (I G /I D ) is more than 1, indicating the presence of partially graphitized carbon structures formed as a result of rearrangement of the carbon structure during the carbonization process, which is advantageous for making superior supercapacitor (SC) electrodes [ 48 ]. XRD patterns of KL and SL were recorded and represented in Figure 2 e. In the case of KL, a diffraction peak was observed at 2θ = 18.7°, while for SL the peak was located at 2θ = 21.6°.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed from differential scanning calorimetry (DSC) ( Figure S1c ) that the KL has glass transition temperature (T g ) at 135 °C, while SL showed lower T g at 80 °C, indicating the early stage softening of SL compared to KL. Rowlandson et al reported the melting of lignin which can produce an intermediate melt region where viscosity is dependent on the S/G ratio [ 48 ]. A low S/G ratio lignin such as KL will have high melt viscosity and difficulty to flow because of the abundance of β-5 linkages which limit the molecular rotation, while a high S/G ratio SL will have a low melt viscosity and hence can flow inside the materials closing the pores generated during carbonization.…”
Section: Resultsmentioning
confidence: 99%
“…In-depth characterisation of the organosolv extracted lignin feedstock was reported in the authors' previous work [56]. The completed experimental design and measured responses are shown in Table 2.…”
Section: Influence Of Factors On Lignin-derived Carbon Propertiesmentioning
confidence: 99%
“…Also, AC carbon fibers from lignin 20,21 with ultramicropores and micropores have been used as interlayer between the cathode and the separator to physically trap the soluble polysulfides. If one considers synthetic materials to start with a material of consistent composition, compared to biomass, phenolic resin has very similar chemical structure to that of lignin, 22 and on crosslinking with an amine, carbonization and activation it yields a microporous carbon material, 22 containing heteroatoms such as nitrogen which increases the conductivity of the cathode host and oxygen which might form groups trapping the soluble polysulfides, such as hydroxyl groups. It is notable that pyridinic nitrogen both traps the soluble polysulfides and acts as an electrocatalyst to accelerate the chain of redox reactions in Li‐S batteries 23 …”
Section: Introductionmentioning
confidence: 99%